Challenges in the Surgical Treatment of Atrioventricular Septal Defect in Children With and Without Down Syndrome in Romania-A Developing Country - Olariu, Ioana-Cristina; Popoiu, Anca; Ardelean, Andrada-Mara; Isac, Raluca; Steflea, Ruxandra Maria; Olariu, Tudor; Chirita-Emandi, Adela; Stroescu, Ramona; Gafencu, Mihai; Doros, Gabriela (Frontiers in Pediatrics, 2021)
Background: Atrioventricular septal defect (AVSD) is a cardiac malformation that accounts for up to 5% of total congenital heart disease, occurring with high frequency in people with Down Syndrome (DS). We aimed to establish the surgical challenges and outcome of medical care in different types of AVSD in children with DS compared to those without DS (WDS). Methods: The study included 62 children (31 with DS) with AVSD, evaluated over a 5 year period. Results: Complete AVSD was observed in 49 (79%) children (27 with DS). Six children had partial AVSD (all WDS) and seven had intermediate types of AVSD (4 with DS). Eight children had unbalanced complete AVSD (1 DS). Median age at diagnosis and age at surgical intervention in complete AVSD was not significantly different in children with DS compared to those WDS (7.5 months vs 8.6). Median age at surgical intervention for partial and transitional AVSDs was 10.5 months for DS and 17.8 months in those without DS. A large number of patients were not operated: 13/31 with DS and 8/31 WDS. Conclusion: The complete form of AVSD was more frequent in DS group, having worse prognosis, while unbalanced AVSD was observed predominantly in the group without DS. Children with DS required special attention due to increased risk of pulmonary hypertension. Late diagnosis was an important risk factor for poor prognosis, in the setting of suboptimal access to cardiac surgery for patients in Romania. Although post-surgery mortality was low, infant mortality before surgery remains high. Increased awareness is needed in order to provide early diagnosis of AVSD and enable optimal surgical treatment.